FENCES AND SEA OWNERSHIP : STUDY OF ENDEMIC MARINE BIOTA CONSERVATION IN INDONESIA ECOLOGICAL INTERPRETATION PERSPECTIVE - Samsul Ariyadi (PT. Jurnal Center Indonesia Publisher, 2025)
Study This to study draft fence sea and ownership of sea areas through ecological interpretation perspective based on interpretation of the Qur'an, with referring to the interpretations of Al-Munir and Al- Maraghi . Approach interdisciplinary between knowledge ecology and religious studies are applied For evaluate role sharia principles in marine biota conservation endemic in Indonesian waters . Methodology analysis content with thematic coding techniques structured used For processing primary and secondary data collected from 2018 to 2023. Case studies that become focus is implementation draft fence sea in several coastal areas of Indonesia, accompanied by analysis legal aspects of ownership sea based on UNCLOS regulations and laws maritime international . Research results show that the ecological interpretation capable give framework philosophical and normative support​ effort conservation , at the same time offer recommendation policy strategic use support marine area management in a way sustainable . Implications results study This expected can encourage constructive dialogue between practitioner law , scholars, and researchers ecology in frame optimization management source Power marine .